2013
DOI: 10.1007/s00586-013-2726-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for survival of 106 surgically treated patients with symptomatic spinal epidural metastases

Abstract: Purpose Evaluation of risk factors for survival in patients surgically treated for symptomatic spinal epidural metastases (SEM). Methods One hundred and six patients who were surgically treated for symptomatic SEM in a 10-year period in two cooperatively working hospitals were retrospectively studied for nine risk factors: age, gender, site of the primary tumor, location of the symptomatic spinal metastasis, functional and neurologic status, the presence of visceral metastases and the presence of other spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 19 publications
2
19
0
3
Order By: Relevance
“…Also of importance are the benefits expected by the patient and the risk of complications, as postoperative complications can cause rapid deterioration in these fragile patients [10][11][12]. Survival in patients with spinal metastases has therefore been the focus of numerous studies, which produced variable results.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also of importance are the benefits expected by the patient and the risk of complications, as postoperative complications can cause rapid deterioration in these fragile patients [10][11][12]. Survival in patients with spinal metastases has therefore been the focus of numerous studies, which produced variable results.…”
Section: Discussionmentioning
confidence: 98%
“…Their median survival was 84 months (95% CI, 41-96). Palliative surgery was performed in 243 patients, whose median survival was 9 months (95% CI, [8][9][10][11]. The survival curves differed significantly between these two groups (P < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10]13,14,15,19,20 Several studies have indicated that surgery is more advantageous than nonoperative measures in terms of functional outcome, pain control, and preservation of ambulatory capacity. 1,2,8,9 Invariably, not all patients with spinal metastases can benefit from a surgical procedure, especially as such interventions may be physiologically taxing to oncology patients and are known to carry moderately high rates of postoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…While surgery can improve overall survival and neurological outcome, and provide pain control, these procedures delay cancer treatments (chemotherapy and radiation) and are resource intensive. 3,14,18,21,22,51 Surgical risk is also high, with postoperative morbidity as high as 76%, 7 which may diminish any benefit of surgery and hasten patient demise.…”
Section: Discussionmentioning
confidence: 99%